Hydrogen enriched combustion in a small spark-ignition engine using a NaOH-based alkaline electrolyzer: experimental evaluation at 0.5 kg/cm² brake load - Suci Rahmadhani Irawan; Ahmad Ilham Wicaksono; Annisa Wulan Sari; Awaludin Martin (Politeknik Negeri Lhokseumawe, 2026)
The increasing concern over greenhouse gas emissions from fossil fuels has driven the exploration of hydrogen as a clean energy source. However, the practical application of hydrogen in internal combustion engines is still limited by the stability of on-demand hydrogen production systems and their integration with conventional engines. This study aims to design and evaluate a NaOH-based alkaline electrolyzer for on-demand hydrogen production and its application in a small spark-ignition engine. The electrolyzer was fabricated using 8 cell stacks with electrode dimensions of 16×16 cm, an inter-electrode gap of 2 mm, and a thickness of 1.2 mm. Experimental tests were conducted at currents of 40 A and 50 A with 30 wt.% NaOH solution. The produced hydrogen gas was directly supplied to a 97cc spark-ignition engine under a constant braking load of 0.5 kg/cm². The result showed that hydrogen production reached 0.9 L/min at 40 A and 1.25 L/min at 50 A. The addition of hydrogen significantly improved engine performance, with brake power increasing by up to 20.8%, brake thermal efficiency by 6.2%, and volumetric efficiency by 9.1%, while reducing brake specific energy consumption by 28%. These findings indicate that hydrogen generated from an alkaline electrolyzer can enhance combustion efficiency and improve overall engine performance, supporting the development of cleaner and more efficient energy systems.